Asymmetry of an epicontinental basin—facies, cycles, tectonics and hydrodynamics: The Triassic Upper Muschelkalk, South Germanic Basin. (28th January 2019) - Warnecke, Matthias; Aigner, Thomas
Abstract: The Middle Triassic–Upper Muschelkalk deposits of central Europe form an excellent, "laboratory‐scale" outcrop analogue for subsurface hydrocarbon reservoirs in epeiric basins. This study provides a detailed sedimentological analysis at microfacies to basin‐wide scales within a well‐constrained biostratigraphic and sequence stratigraphic framework. The database comprises 31 outcrops and 27 drill cores in the southern part of the Triassic Germanic Basin, from Luxembourg, eastern France, northern Switzerland and southwestern Germany. The Upper Muschelkalk comprises 21 lithofacies types which are grouped into eight distinct lithofacies associations encompassing coastal sabkha, peritidal, backshoal, shoal, shoal fringe, foreshoal to offshoal environments. A 1D sequence stratigraphic framework was established on different cyclic scales ranging from depositional sequences, cycle sets, cycles to mini‐cycles. Regional 2D correlations based on 1D cycle analysis and biostratigraphic conodont/ceratite zonation reveal the temporal and spatial distribution of reservoir bodies and the morphological variance of 1D cycles across the carbonate ramp. A basin‐wide W–E 'coast to coast' cross‐section shows an asymmetric basin architecture with significant differences in facies distribution, cycle morphology, and consequently sizes of potential reservoir bodies. This distinct asymmetry is controlled by the palaeo‐tectonic setting (quiet versus more active) and the hydrodynamics (windward versus leeward, inflow of freshwater versus marine waters) which differs from coast to coast. Such asymmetric patterns will have to be considered in exploration scenarios of subsurface hydrocarbon‐bearing epeiric basins in the Middle East and elsewhere. Abstract : This study provides a detailed sedimentological analysis of the Middle Triassic Upper Muschelkalk at micro‐to basin scale within a well constrained bio‐ and sequence‐stratigraphic framework. It reveals an asymmetric basin architecture with significantly differences in facies distribution, cycle morphology, hydrodynamics and sizes of potential reservoir bodies.